Spatial Frequency Analysis of Luminal Surface Roughness of the Carotid Artery Measured by Ultrasound - Yamane, Ryota; Mori, Shohei; Arakawa, Mototaka; Wilhjelm, Jens E.; Kanai, Hiroshi (IEEE International Ultrasonics Symposium (Online), 2023)
For early detection of atherosclerosis, we have developed a method to measure minute surface roughness by utilizing the natural longitudinal displacement of the intima-media complex on the carotid artery caused by pulsation. In this study, the surface roughness of three healthy subjects in their 20s were measured using this method to investigate the spatial frequency characteristics of surface roughness. As a result, the spatial frequency spectrum showed a similar tendency in all subjects.